Methods for Investigating Trace Element Binding in Sediments - Linge, Kathryn (Taylor & Francis Group, 2008)
Sediments play an important role in maintaining water quality. This review describes methods of investigating element binding in sediments, and assesses the value of each for characterizing sediment contamination. Although easy to obtain, data from "bulk" tests such as fractionation schemes or fitting adsorption isotherms cannot describe binding or phase composition definitively. Modern spectroscopic techniques can investigate the sediment surface on a molecular scale, but are not yet used routinely for sediment analysis. Proper assessment of the implications of sediment contamination normally requires more than one method to be used. Comparing contaminant remobilization rates to the time scales of environmental factors causing remobilization is also important.